Islamic Religious Learning Strategy Through Spiritual Intelligence Approach and Strengthening Local Values ​​at Attaqwa Foundation, Ujungharapan, Bekasi - Haikal Fathurrizqi; Ma'rifah, Iza; Aca syathybie; Liana fadhliatul husnah (CV. Kalimasada Group, 2025)
Purpose- This study explores the strategy of Islamic religious learning through the integration of a spiritual intelligence approach and the strengthening of local values at the Attaqwa Foundation, Ujungharapan, Bekasi. The research aims to understand how spiritual intelligence can be internalized in religious education and how local wisdom contributes to the development of learners’ moral and spiritual character. Design/Methodology/Approach - Employing a qualitative-descriptive method, data were collected through interviews, observation, and documentation involving teachers, students, and community figures. Findings - The findings indicate that the Attaqwa Foundation adopts a holistic strategy that combines cognitive, affective, and spiritual dimensions of learning. Spiritual intelligence is developed through reflective practices, religious rituals, and ethical modeling, while local values are integrated through community-based activities and contextual teaching. This synergy not only enhances students’ religious understanding but also fosters a strong sense of identity and social responsibility. Originality/Value - The study concludes that the combination of spiritual intelligence and local values forms an effective model for religious learning in a pluralistic society.